Odpowiedzi

2010-03-23T15:15:48+01:00
A)1/3x-2=x+2 *3
x-6=3x +6
-12=2x /2
x=-6
b)1-6/7x=4/7 *7
7-6x=4
3=6x /6
x=0,5
c)6 (1/4x-2)=18
1,5x - 12=18
1,5x=30 /1,5
x=20
d)x/6-1/6=1 *6
x-1=1
x=2
e)-2(2x-1) = x/3 ?????gdzie jest =
jeżeli tu to tak
*3
-6(6x-3)=x
-36x+18=x
18=-35x
x=-0,51

f)2/5 (3-x)=-2 *5
2 (15-5x) = -10
30 -10x = -10
40=10x /10
x=4
g)3/4 (2-3x)=-6 *4
3 (8-12x)= -24
18 - 36x=-24
42=36x /36
x=1,17

h)1,5(x-3) =9-x
1,5x- 4,5= 9-x
2,5x= 13,5 /2,5
x=5,4

i)0,6 + x/2=x+1 *10
6+ 5x= 10x+10
5x=-4 /5
x= -4/5
2 1 2
2010-03-23T15:19:24+01:00
A) 1/3x-2 = x+2
⅓x - x = 2 + 2
-⅔x = 4 / × (-3/2)
x = -6

b)1-6/7x = 4/7
-6/7x = 4/7 - 1
-6/7x = -3/7 / ×(-7/6)
x = ½

c)6(1/4x-2) = 18
2/3x - 2 = 18
2/3x = 18+2
2/3x = 20 / × 3/2
x = 30

d) x/6-1/6 = 1 / ×6
x - 1 = 6
x = 7

e) -2(2x-1) = x/3 / ×3
-2(2x-1) = x
-4x +2 = x
-4x - x = -2
-5x = -2 / :(-5)
x = 2/5

f) 2/5(3-x) = -2
6/5 - 2/5x = -2
-2/5x = -2 - 1⅕
-2/5x = -3⅕ /× (-5/2)
x = 8

g) 3/4(2-3x) = -6
1½ - 1½x = -6
- 1½x = -6 - 1½
- 1½x =-7½ / × (-2/3)
x = 5

h) 1/5(x-3) = 9-x
1/5x - 3/5 = 9 -x
1/5x + x = 9 + 3/5
1⅕x = 9 i 3/5 / 5/6
x = 8

i) 0,6+x/2 = x+1 / ×2
1,2 + x = 2x + 2
x - 2x = 2 - 1,2
-x =0,8 / ×(-1)
x = -0,8
3 4 3